Integrated Management of the Coastal Marine Areas of the province of Pacasmayo, La Libertad. Peru - Nakasone Santivañez, Erich David (2019)
The objective of this research is to evaluate the Integrated Management of Coastal Marine Areas in the province of Pacasmayo. The proposed methodology is based on the Manual for the measurement of progress and the direct effects of the integrated management of coasts and oceans. Published by UNESCO in the year 2006. The research consisted in the analysis of 16 governance indicators. Each indicator was evaluated and assigned a numerical value so that they can be analyzed by descriptive and inferential statistical tools. The results show that for the province of Pacasmayo there are deficiencies in the planning and management process of the coastal marine zone.